2003
DOI: 10.1177/1534735403002002004
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens in Botanical Dietary Supplements: Implications for Cancer

Abstract: Phytoestrogens are plant constituents that possess either estrogenic or antiestrogenic activity. Although their activities are weak as compared with human endogenous estrogens, the consumption of phytoestrogens may have clinically significant consequences. A number of botanicals, or the compounds contained therein, have been identified as putative estrogenic agents, but consensus in the biomedical community has been hampered by conflicting data from various in vitro and in vivo models of estrogenic activity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 161 publications
2
48
0
5
Order By: Relevance
“…1B). Red clover has been tested in clinical trials as a menopause therapy (27) with formulations based on the active metabolites and their metabolic precursors (13). In the present study we confirmed the presence of 8-PN as the most potent estrogen in hops using a mass spectrometry-based screening assay developed in our laboratory (28).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…1B). Red clover has been tested in clinical trials as a menopause therapy (27) with formulations based on the active metabolites and their metabolic precursors (13). In the present study we confirmed the presence of 8-PN as the most potent estrogen in hops using a mass spectrometry-based screening assay developed in our laboratory (28).…”
Section: Introductionsupporting
confidence: 71%
“…The strobiles of Humulus lupulus L. (hops) are primarily used to flavor beer, although it has been studied since 1953 for a potential estrogenic mechanism of action (13)(14)(15). In the past, the flavonoids, 8-prenylnaringenin (8-PN), 6-prenylnaringenin (6-PN), and the chalcone, isoxanthohumol (IX), have been isolated and reported to be estrogenic in vitro and/or in vivo (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The strobiles of Humulus lupulus L. (Cannabaceae) (hops) are primarily used to flavor beer, and have been studied since 1953 for a potential estrogenic mechanism of action [13][14][15]. In the past, the flavonoids 8-PN and 6-PN, and the chalcone, isoxanthohumol (IX), have been isolated and reported to be estrogenic in vitro and/or in vivo [16,17].…”
mentioning
confidence: 99%
“…Herbal therapies with estrogenic, androgenic, or progesterone-like activity are a theoretic concern for patients with hormone-sensitive cancers, particularly breast, ovarian, endometrial, or prostate cancers [54]. However, the majority of the literature on hormonal effects of herbs focuses on the estrogen activity of herbs commonly used for treating menopause.…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%